2002
DOI: 10.1074/jbc.m108895200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Baculovirus DNA Elements Strongly Stimulate Activities of Exogenous and Endogenous Promoters

Abstract: A DNA sequence upstream from the polyhedrin gene of baculovirus Autographa californica nucleopolyhedrovirus (AcMNPV) was found to activate strongly the expression of full or minimal promoters derived from AcMNPV and other sources. Promoters tested included the minimal CMV (CMVm) promoter from human cytomegalovirus, the full heat shock 70 promoter from Drosophila, and the minimal p35 promoter from baculovirus. Deletion and mutagenesis analyses showed that this functional polyhedrin upstream (pu) activator seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…We have previously found that IE1 and IE2 can activate some early baculovirus promoters within Vero E6 cells (24). To test whether they also activate the mammalian CMV promoter, we cotransfected IE1-or IE2-expressing plasmids with the reporter plasmid pAcL (where CMV drives the luciferase gene) or pA h cL (where CMV drives luciferase with an additional hr1 baculovirus enhancer) (26). We found that IE2 dramatically improved the CMV promoter-driven luciferase activity, which increased 122-fold in the presence of the hr1 sequence and over 25-fold without the hr1 sequence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that IE1 and IE2 can activate some early baculovirus promoters within Vero E6 cells (24). To test whether they also activate the mammalian CMV promoter, we cotransfected IE1-or IE2-expressing plasmids with the reporter plasmid pAcL (where CMV drives the luciferase gene) or pA h cL (where CMV drives luciferase with an additional hr1 baculovirus enhancer) (26). We found that IE2 dramatically improved the CMV promoter-driven luciferase activity, which increased 122-fold in the presence of the hr1 sequence and over 25-fold without the hr1 sequence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(B) DpnI digestion showed that subfragments p143-2 and p143-3 can function as replication origins in Sf-21 cells in the presence of baculovirus infection. Sf-21 cells were transfected with plasmids containing the indicated baculovirus genomic regions and pABpLhGFP (11) and pABhcmEpL, which contain egfp and hr1 elements, respectively, and which served as the necessary positive and negative controls, respectively, followed by AcMNPV infection at an MOI of 1. ity is located in the overlapping region between p143-2 and p143-3. It has been reported previously that a plasmid containing the p143 gene sequence can replicate in the presence of baculovirus infection, indicating that an element in the sequence of this gene can function as a replication origin (14).…”
Section: Resultsmentioning
confidence: 99%
“…The transfected/infected cells were harvested at 48 h postinfection for luciferase activity assays. The detailed procedures were described previously (11). The luciferase activity data (average Ϯ standard deviation) were collected from triplicate assays of three independent transfections and are presented as the number of relative light units (RLUs) per microgram protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4) We cloned the hr3 fragment from the BmNPV ZJ8 genome (Genbank accession No. U51328) and found that it can function as the origin of viral DNA replication and increase the transcriptional activity of viral gene promoters such as helicase and gp64 and of nonviral gene promoters such as hsp70 from Drosophila.…”
mentioning
confidence: 99%